Total ionization dose and single event effects of a commercial stand-alone 4 Mb resistive random access memory (ReRAM). (September 2019) - Bi, J.S.; Li, B.; Xi, K.; Luo, L.; Ji, L.L.; Wang, H.B.; Liu, M.
Abstract: Experiments on total ionizing dose (TID) by cobalt-60 and single event effects (SEE) by pulsed laser and heavy ions were conducted on a 4 Mb commercial ReRAM from Fujitsu. The bit cell features two-transistor-two-resistor (2T2R) architecture and a TaOx -based ReRAM stack. The TID failure levels and recovery trend after annealing are strongly related to operation modes. The static mode tolerates a TID dose up to 130 krad(Si), whereas the dynamic mode fails during a TID range from 20 to 70 krad(Si). The cross-section of single event function interruption (SEFI) in ReRAM was determined by heavy ions and confirmed with a pulsed laser sensitivity scan. The threshold LET for the most sensitive region is less than 5 MeV∙cm 2 /mg. Failure mechanisms are discussed in detail. These results and discussions are useful for developing radiation-hard ReRAM for use in space applications. Highlights: TID and SEEs of a 4 Mb resistive random access memory are proposed. The TID failure levels are strongly related to operation modes. SEFI are observed and located in the peripheral circuits via pulsed laser scan.